1997
DOI: 10.1063/1.364793
|View full text |Cite
|
Sign up to set email alerts
|

Flash annealing and magnetic interactions in Pr4Fe78B18

Abstract: Enhanced-remanence Pr4Fe78B18 alloys were produced by using a high heating rate/short time anneal, known as flash annealing. Partially amorphous ribbons were produced by melt spinning and then annealed for 10–20 s at temperatures 600–820 °C by passing current through the sample. Coercivity increases of up to 15% were systematically observed in relation to furnace-annealed material. Mössbauer spectra showed that flash annealing resulted in significant amounts of Pr2Fe23B3 and reduced quantities of α-Fe. Our bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…For further improving the magnetic properties, we therefore adopt Nd to substitute for Pr in the (Pr 1−x Nd x ) 8.5 Fe 79.5 Ti 2 B 10 ribbons. Table 1 10 , where x = 0-0.5. It is shown that with increasing Nd content, B r increases from 9.6 kG for x = 0-9.9 kG for x = 0.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For further improving the magnetic properties, we therefore adopt Nd to substitute for Pr in the (Pr 1−x Nd x ) 8.5 Fe 79.5 Ti 2 B 10 ribbons. Table 1 10 , where x = 0-0.5. It is shown that with increasing Nd content, B r increases from 9.6 kG for x = 0-9.9 kG for x = 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…The boron concentrations of nanocomposites with either low (∼5-7 at%) [5][6][7][8][9] or extreme high (∼16-20 at%) [10,11] in the Pr-lean PrFeB series ribbons are normally employed to develop ␣-Fe/Pr 2 Fe 14 B and Fe 3 B/Pr 2 Fe 14 B types nanocomposites, respectively, by melt spinning [5][6][7][8][9][10][11], resulting in a lower intrinsic coercivity i H c of less than 8 kOe, which limits their application at higher temperatures (T > 100 • C).…”
Section: Introductionmentioning
confidence: 99%
“…Boron concentration with either low (∼5-7 at) [5][6][7][8][9] or extreme high (∼16-20 at) [10,11] in Pr-lean PrFeB series ribbons are normally selected to develop ␣-Fe/Pr 2 Fe 14 B and Fe 3 B/Pr 2 Fe 14 B types nanocomposites, respectively, by melt spinning in various research groups [5][6][7][8][9][10][11], but the intrinsic coercivity i H c of those nanocomposites obtained so far is quite lower, resulting from the existence of considerable amount of the magnetically soft phases ␣-Fe or Fe 3 B. These magnets for higher temperature (T > 100 • C) applications are * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…From thermal magnetic analysis (TMA), it was found that all the selected refractory elements (Cr, Nb, V, Ti and Zr) were easy to react with excess boron and retard the formation of [3,4], with excellent remanence B r and maximum energy product (BH) max have been investigated extensively for making bonded magnets. Boron concentration with either low (~ 5-7 at%) [5][6][7][8][9] or extreme high (~16 -20 at%) [10,11] in Pr-lean PrFeB series ribbons are normally selected to develop α-Fe/Pr 2 Fe 14 B and Fe 3 B/Pr 2 Fe 14 B types nanocomposites, respectively, by melt spinning, in various research groups [5][6][7][8][9][10][11], but the intrinsic coercivity i H c of those nanocomposites obtained so far is quite lower, resulting from the existence of considerable amount of magnetically soft phases α-Fe or Fe 3 B. These magnets for higher temperature (T > 100 o C) applications are constrained by lack of sufficient i H c , hence, coercivity needs to be further increased for some practical usages.…”
mentioning
confidence: 99%